Endovascular management of transplant renal artery stenosis: early and mid-term results - Pinto,Vanda (2021)
Abstract Objective: Renal graft dysfunction or worsened hypertension in renal transplanted patients may be a manifestation of graft hypoperfusion due to transplant renal artery stenosis (TRAS) or stenosis of iliac arteries proximal to renal transplant (pseudo-TRAS). Endovascular management of TRAS has been increasingly used to preserve renal graft function. With this study, we aim to evaluate the impact of endovascular treatment of TRAS on renal function in the short to medium term. Material and methods: This is an observational, retrospective, single-center study that included all adult renal transplant patients who underwent endovascular intervention on TRAS between September 2017 and June 2020. Renal graft function was monitored by serum Creatinine (sCr) levels. Results: Thirteen patients were included (53.8% female), with a median age of 57 (21-70) years. Eleven patients (84.6%) presented with graft dysfunction. Ten subjects (76.9%) underwent transluminal angioplasty and stenting of renal artery and three (23,1%) of donor iliac arteries. Most cases (69.2%) were interventioned in the first-year post-transplant. Overall technical success was 100%, with no periprocedural deaths. Overall 30-day morbidity was 15.4%. Median follow-up time was 20.2 (1,3 - 36,3) months. One patient died during follow up and other worsened graft dysfunction, requiring hemodialysis and nephrectomy. Reduction in sCr levels was statistically significant in the first postoperative month, compared to preoperative values, but sCR levels were still increased when compared to baseline levels (pre-TRAS diagnosis). Conclusions: The majority (12/13) of patients showed improvement or stabilization of renal graft function compared to the preoperative period, during the follow-up period, supporting the procedure’s safety. Despite this, most patients did not recover baseline sCr levels, reinforcing the importance of prompt graft revascularization. Delayed diagnosis of TRAS may compromise the benefit of revascularization and prevent full recovery of renal function.